Swapping of The N-Terminal Domain of Human Topoisomerase 1B with the Corresponding Plasmodium Falciparum Counterpart Strongly Impairs Enzyme Activity - Dasari, Jagadish Babu (Varastegan Institute for Medical Sciences, 2020)

(untitled) (Rep Biochem Mol Biol)
BACKGROUND: DNA topoisomerases 1B are a class of ubiquitous enzyme that solves the topological problems associated with biological processes such as replication, transcription and recombination. Numerous sequence alignment of topoisomerase 1B from different species shows that the lengths of different domains as well as their amino acids sequences are quite different. In the present study a hybrid enzyme, generated by swapping the N-terminal of Plasmodium falciparum into the corresponding domain of the human, has been characterized. METHODS: The chimeric enzyme was generated using different sets of PCR. The in vitro characterization was carried out using different DNA substrate including radio-labelled oligonucleotides. RESULTS: The chimeric enzyme displayed slower relaxation activity, cleavage and re-ligation kinetics strongly perturbed when compared to the human enzyme. CONCLUSION: These results indicate that the N-terminal domain has a crucial role in modulating topoisomerase activity in different species.